A glass shatter-resistant packaging structure and a packaging method thereof

CN122915546APending Publication Date: 2026-10-16杭州谷优进出口有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611362188.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]针对现有技术中存在的缓冲吸能效率低、局部应力集中、抗静电性差、阻燃性弱、长期力学稳定性不足等问题,本发明提供了一种玻璃耐摔包装结构及其包装方法

Benefits of technology

蓖麻油基聚氨酯预聚体作为复合软垫基体,可提供基本的柔韧性、回弹性与成型性;聚烯烃弹性体能够改善复合软垫的韧性与弹性,提高其断裂伸长率与抗冲击强度;相变复合填料可高效耗散冲击能量,提升缓冲吸能效果;磷氮型动态交联长效抗静电剂使复合软垫兼具阻燃与抗静电功能,并提升材料韧性;多维无机增强填料可提高复合软垫抗压强度,分散冲击应力并降低材料密度;复合发泡剂使复合软垫形成适配缓冲需求的泡孔结构,为能量吸收提供空间;硅烷偶联剂改善无机填料与有机基体的界面结合力,减少界面缺陷,提升力学性能稳定性;复合助剂可分别起到抑制热氧老化、稳定泡孔结构、改善加工流动性、抑制霉菌生长及提升相变组分分散性的作用;扩链催化剂可加速基体与抗静电剂的反应,提高复合软垫的力学强度与成型效率;补孔调节剂可填充发泡过程中产生的微小针孔,提高泡孔致密性,进一步优化缓冲性能;上述各组分相互配合,使复合软垫具备良好的缓冲、阻燃、抗静电及力学性能,搭配泡沫板与包装箱体,可对玻璃产品起到有效的防护作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122915546A_ABST
    Figure CN122915546A_ABST
Patent Text Reader

Abstract

The application provides a glass drop-resistant packaging structure and a packaging method thereof, which comprises a packaging box body and a buffer structure arranged in the packaging box body, the buffer structure comprises a foam plate and a composite soft pad, and the foam plate and the composite soft pad are connected with the inner wall of the packaging box body; the raw materials of the composite soft pad comprise, in parts by weight, castor oil-based polyurethane prepolymer 45-60 parts, polyolefin elastomer 8-15 parts, phase change composite filler 5-12 parts, phosphorus-nitrogen type dynamic cross-linking long-acting antistatic agent 6-10 parts, multi-dimensional inorganic reinforcing filler 4-8 parts, composite foaming agent 6-12 parts, silane coupling agent 1-3 parts, composite additive 3.2-6.5 parts, chain extension catalyst 0.2-0.6 parts and hole-filling regulator 0.2-0.5 parts. The components in the application cooperate with each other, so that the composite soft pad has good buffering, flame-retardant, antistatic and mechanical properties, and the foam plate and the packaging box body can effectively protect the glass product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of packaging structure technology, specifically to a glass shatterproof packaging structure and its packaging method. Background Technology

[0002] Glass products, characterized by their transparency, heat resistance, and good chemical stability, are widely used in construction, home furnishings, electronics, and medical fields. However, due to their brittleness and poor impact resistance, they are easily damaged by collisions and drops during handling, storage, and transportation. This places stringent requirements on the cushioning, energy absorption, impact resistance, and structural stability of packaging structures. Currently, glass products are mostly packaged using foam padding, honeycomb cardboard, or ordinary polyurethane cushioning in conjunction with packaging boxes. While this provides basic protection, problems such as insufficient cushioning, localized stress concentration, and susceptibility to breakage still exist under complex transportation conditions such as drops, impacts, and vibrations, as well as long-term storage and transportation conditions.

[0003] Existing cushioning materials generally suffer from insufficient energy absorption efficiency and low impact resistance, making it difficult to quickly dissipate drop and impact energy, which can easily lead to localized stress concentration and breakage of the glass. At the same time, most cushioning materials cannot simultaneously achieve flame retardancy, antistatic properties, and long-term mechanical stability. They have weak interfacial bonding and uneven cell structure, which not only reduces the reliability of protection but also easily generates static electricity accumulation and insufficient flame retardancy, making it difficult to meet the comprehensive protection requirements of high-end glass products. Summary of the Invention

[0004] In view of the problems existing in the prior art, such as low buffer energy absorption efficiency, local stress concentration, poor antistatic properties, weak flame retardancy, and insufficient long-term mechanical stability, the present invention provides a glass drop-resistant packaging structure and packaging method thereof.

[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention discloses a glass impact-resistant packaging structure, including a packaging box and a cushioning structure disposed within the packaging box. The cushioning structure includes a foam board and a composite cushion, both of which are connected to the inner wall of the packaging box. By weight, the raw materials for preparing the composite cushion include: 45-60 parts of castor oil-based polyurethane prepolymer, 8-15 parts of polyolefin elastomer, 5-12 parts of phase change composite filler, 6-10 parts of phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, 4-8 parts of multidimensional inorganic reinforcing filler, 6-12 parts of composite foaming agent, 1-3 parts of silane coupling agent, 3.2-6.5 parts of composite additives, 0.2-0.6 parts of chain extender catalyst, and 0.2-0.5 parts of pore-filling regulator.

[0006] Using the above technical solutions, castor oil-based polyurethane prepolymer, as the composite cushion matrix, provides basic flexibility, resilience, and formability; polyolefin elastomers improve the toughness and elasticity of the composite cushion, increasing its elongation at break and impact strength; phase change composite fillers efficiently dissipate impact energy, enhancing the cushioning and energy absorption effect; phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agents give the composite cushion both flame retardant and antistatic functions, and improve material toughness; multidimensional inorganic reinforcing fillers improve the compressive strength of the composite cushion, disperse impact stress, and reduce material density; composite foaming agents enable the composite cushion to form a cell structure adapted to cushioning needs, providing space for energy absorption; silane coupling agents improve the non-... The interfacial bonding force between the mechanical filler and the organic matrix reduces interfacial defects and improves the stability of mechanical properties. The composite additives can respectively inhibit thermo-oxidative aging, stabilize the cell structure, improve processing fluidity, inhibit mold growth, and improve the dispersibility of phase change components. The chain extender catalyst can accelerate the reaction between the matrix and the antistatic agent, and improve the mechanical strength and molding efficiency of the composite cushion. The pore filling regulator can fill the tiny pinholes generated during the foaming process, improve the cell density, and further optimize the cushioning performance. The above components work together to give the composite cushion good cushioning, flame retardancy, antistatic and mechanical properties. When combined with foam board and packaging box, it can effectively protect glass products.

[0007] Preferably, the multidimensional inorganic reinforcing filler is composed of basalt whiskers and hollow glass microspheres in a mass ratio of 1-2:1, the silane coupling agent is one of KH-550, KH-560 or KH-570, and the pore filling regulator is polyethylene glycol PEG-600.

[0008] Using the above technical solution, the multidimensional inorganic reinforcing filler is composed of basalt whiskers and hollow glass microspheres in a mass ratio of 1-2:1. The basalt whiskers can improve the compressive strength of the composite cushion, while the hollow glass microspheres can disperse impact stress and reduce the overall density of the material. The silane coupling agent is one of KH-550, KH-560, or KH-570, which can improve the interfacial bonding force between the multidimensional inorganic reinforcing filler and the organic matrix and reduce interfacial defects. The pore filling regulator is polyethylene glycol PEG-600, which can fill the tiny pinholes generated during the foaming process and improve the compactness of the composite cushion's pore structure.

[0009] Preferably, the composite foaming agent is composed of 4-8 parts of modified azodicarbonamide, 1-2 parts of talc, and 1-2 parts of sodium bicarbonate, wherein the modified azodicarbonamide has a decomposition temperature of 150-170℃; the composite additive is composed of 0.5-1.5 parts of antioxidant 1010, 1-2 parts of polyether modified silicone oil, 0.3-0.8 parts of zinc stearate, 0.2-0.6 parts of 1,2-benzisothiazolin-3-one, and 1.2-1.6 parts of ethylene-vinyl acetate copolymer; the chain extender catalyst is a compound of an organic bismuth catalyst and dibutyltin dilaurate in a mass ratio of 1-2:1.

[0010] Using the above technical solutions, in the composite foaming agent, the modified azodicarbonamide decomposes to generate the gas required for foaming, talc can induce the formation of a fine cell structure, and sodium bicarbonate can regulate the foaming rate; in the composite additives, antioxidant 1010 can inhibit thermal oxidative aging during material processing and use, polyether-modified silicone oil can regulate the cell structure and maintain its stability, zinc stearate can improve the material's processing fluidity, 1,2-benzisothiazolin-3-one can inhibit mold growth in humid environments, and ethylene-vinyl acetate copolymer can improve the dispersion of phase change components in the matrix and its compatibility with the polyurethane matrix; in the chain extender catalyst, the organic bismuth catalyst works in conjunction with dibutyltin dilaurate to accelerate the reaction between the matrix resin and related components, regulate the material's crosslinking density, and improve the material's mechanical strength and molding efficiency.

[0011] Preferably, the phase change composite filler is halloysite / high-pressure resistant microcapsule paraffin phase change composite filler, and its preparation raw materials include, by weight: 25-35 parts paraffin, 0.5-1.0 parts sodium dodecylbenzenesulfonate, 8-12 parts melamine, 20-30 parts formaldehyde solution with a mass fraction of 35-37%, 2-4 parts hexamethylenediamine, 0.5-1.5 parts triethanolamine, 0.5-1.0 parts nano silica, 8-12 parts halloysite nanotubes, 4-6 parts 3-aminopropyltriethoxysilane, 1.5-2.5 parts dopamine hydrochloride, 150-250 parts tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and 180-220 parts anhydrous toluene.

[0012] Using the above technical solutions, paraffin wax can exert phase change energy absorption; sodium dodecylbenzenesulfonate can assist paraffin wax in forming a uniform emulsion; melamine, in synergy with formaldehyde solution (35-37% by mass), hexamethylenediamine, and triethanolamine, can prepare microcapsule wall materials; nano-silica can participate in the composition of microcapsule wall materials; halloysite nanotubes can serve as carriers to load microcapsules; 3-aminopropyltriethoxysilane can modify halloysite nanotubes; dopamine hydrochloride can form a coating layer on the surface of modified halloysite nanotubes; tris(hydroxymethyl)aminomethane hydrochloride buffer can adjust the pH value of the system, providing a suitable environment for dopamine self-polymerization; anhydrous toluene can serve as a dispersion medium to assist in the dispersion and modification reaction of halloysite nanotubes.

[0013] Preferably, the preparation method of the phase change composite filler includes the following steps: 1) Heat the paraffin to 55-65℃ to melt it, add sodium dodecylbenzenesulfonate and 3-4 times the weight of deionized water, and stir at 1500-2500 r / min for 30-50 min to form a uniform emulsion. 2) Mix melamine, formaldehyde solution, and hexamethylenediamine, add nano-silica, and add triethanolamine dropwise to adjust the pH of the system to 8.5-9.5. Stir the mixture in a water bath at 70-80℃ at a speed of 300-500r / min for 1-2 hours to obtain the prepolymer. 3) Add the prepolymer to the emulsion and stir at 300-500 r / min at 80-90℃ for 3-5 h. After cooling to 25-30℃, centrifuge at 7000-9000 r / min for 15-25 min. Wash the precipitate with anhydrous ethanol 3-4 times, and then dry it at 45-50℃ and vacuum degree -0.09~-0.095 MPa for 7-9 h. After pulverizing, pass it through a 200-240 mesh sieve to obtain nano-reinforced high pressure resistant microcapsule-coated paraffin. 4) Dry halloysite nanotubes at 115-125℃ and vacuum degree -0.09~-0.095MPa for 3-5h, cool to 25-30℃ and add to anhydrous toluene. Sonicate disperse for 25-35min under ultrasonic power of 300-400W and frequency of 30-40kHz. Add 3-aminopropyltriethoxysilane, heat to 80-90℃ and reflux for 6-8h under nitrogen protection and stirring at 300-500r / min. 5) After the reaction is complete, the reaction solution obtained in step 4) is centrifuged at 7000-9000 r / min for 15-25 min. The precipitate is washed 3-4 times with anhydrous ethanol and then dried at 55-65℃ and vacuum degree -0.09~-0.095MPa for 5-7 h to obtain aminated halloysite nanotubes. The aminated halloysite nanotubes are mixed with deionized water at a mass ratio of 1:10-15, dopamine hydrochloride is added, and the pH of the system is adjusted to 8.0-8.5 with tris(hydroxymethyl)aminomethane hydrochloride buffer. The mixture is stirred at 250-350 r / min at 25-30℃ for 10-14 h. 6) After the reaction is complete, the reaction solution obtained in step 5) is centrifuged at 7000-9000 r / min for 15-25 min. The precipitate is washed with anhydrous ethanol 3-4 times, and then dried at 55-65℃ and vacuum degree -0.09~-0.095MPa for 7-9 h to obtain dopamine modified halloysite nanotubes. 7) Add dopamine-modified halloysite nanotubes and paraffin-coated nano-reinforced high-pressure microcapsules obtained in step 3) to a high-speed mixer at a mass ratio of 1:1.2-1.8. Stir at 1200-1800 r / min for 15-25 min at 55-65℃. After cooling to 25-30℃, grind and pass through a 200-240 mesh sieve to obtain phase change composite filler.

[0014] Using the above technical solution, a uniform emulsion is formed by mixing molten paraffin with sodium dodecylbenzenesulfonate and deionized water, providing a stable dispersion system for subsequent microcapsule encapsulation. A prepolymer prepared by reacting melamine, formaldehyde solution, hexamethylenediamine, and nano-silica can encapsulate the paraffin in the emulsion. After centrifugation, washing, drying, and sieving, nano-reinforced high-pressure resistant microcapsules encapsulating paraffin are obtained. Nano-silica can improve the structural strength and high-temperature resistance of the microcapsules. Halloysite nanotubes are dried, ultrasonically dispersed, modified with silane, and centrifuged, washed, and dried to obtain aminated halloysite nanotubes, which are then modified with dopamine hydrochloride. Dopamine-modified halloysite nanotubes were obtained after centrifugation, washing, and drying. This modification treatment can improve the interfacial compatibility of halloysite nanotubes. After mixing, stirring, grinding, and sieving, the dopamine-modified halloysite nanotubes and nano-reinforced high-pressure resistant microcapsules coated with paraffin are uniformly loaded on the surface of the dopamine-modified halloysite nanotubes. The resulting phase change composite filler has nano-reinforcement, phase change energy absorption, and good interfacial compatibility. It can improve its bonding effect with the composite cushion matrix of the packaging structure. At the same time, energy absorption is achieved through phase change, and the structural stability of the filler is improved through nano-reinforcement.

[0015] Preferably, the raw materials for preparing the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, by weight, include: 20-25 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 15-20 parts of toluene diisocyanate, 0.2-0.4 parts of dibutyltin dilaurate, 90-110 parts of polyetheramine, and 0.4-0.6 parts of polymethyl methacrylate microspheres.

[0016] Using the above technical solutions, DOPO can exert both gas-phase and condensed-phase flame-retardant effects; toluene diisocyanate can undergo an addition reaction with DOPO and a grafting reaction with polyetheramine; dibutyltin dilaurate can catalyze the addition reaction between DOPO and toluene diisocyanate, thereby increasing the grafting rate; polyetheramine can provide hydrophilic segments to achieve antistatic effects; polymethyl methacrylate microspheres can be uniformly dispersed in the system, playing a physical anchoring and stabilizing role for the hydrophilic segments of polyetheramine.

[0017] Preferably, the preparation method of the phosphorus-nitrogen type dynamically crosslinked long-lasting antistatic agent includes the following steps: (1) Add DOPO, toluene diisocyanate and dibutyltin dilaurate to a reaction vessel, heat to 90-100℃, and stir at 350-450r / min for 3-5h under nitrogen protection to obtain an intermediate; (2) Cool the intermediate to 55-65℃, add polyetheramine and polymethyl methacrylate microspheres, heat to 70-80℃, stir at 250-350r / min for 3-4h to obtain phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent.

[0018] Using the above technical solution, DOPO and toluene diisocyanate react under the catalysis of dibutyltin dilaurate in a nitrogen-protected environment at 90-100℃ to generate an intermediate containing phosphorus and nitrogen active groups. The intermediate further reacts with polyetheramine and polymethyl methacrylate microspheres at 70-80℃, which enables the hydrophilic segments of polyetheramine to be controllably grafted and retains suitable migration ability. The polymethyl methacrylate microspheres can form a physical dispersion anchoring effect on the polyetheramine segments, thereby obtaining a phosphorus and nitrogen type dynamic crosslinking long-lasting antistatic agent with phosphorus and nitrogen synergistic flame retardancy, long-lasting antistatic effect and dynamic crosslinking properties.

[0019] Preferably, the method for preparing the composite cushion includes the following steps: a. Raw material pretreatment: The castor oil-based polyurethane prepolymer and polyolefin elastomer are dried at 75-85℃ and a vacuum of -0.09 to -0.095 MPa for 3-5 hours; the multidimensional inorganic reinforcing filler is dried at 105-115℃ for 1.5-2.5 hours; and the phase change composite filler is dried at 45-50℃ and a vacuum of -0.09 to -0.095 MPa for 0.5-1.5 hours. b. Premixing and dispersing: The dried castor oil-based polyurethane prepolymer, the dried polyolefin elastomer, the dried multidimensional inorganic reinforcing filler, the silane coupling agent, the composite additive, and the chain extender catalyst are added to a high-speed mixer and stirred at 1300-1500 r / min at 25-30℃ for 20-25 min. Then, the dried phase change composite filler and the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent are added and stirred at 1600-2000 r / min at 40-50℃ for 30-40 min to obtain a mixed slurry. c. Melt blending: The mixture slurry is added to a twin-screw extruder. The temperature gradient of each section of the extruder is set as follows: Zone 1 140-150℃, Zone 2 150-160℃, Zone 3 160-170℃, and the die head 150-160℃. The screw speed is 250-350 r / min. After melt blending, the mixture is pelletized to obtain foamed masterbatch. d. Foaming molding: Mix the foaming masterbatch, composite foaming agent, and pore filling regulator evenly, add it to the injection molding foaming machine, injection temperature 150-160℃, mold temperature 50-60℃, injection pressure 8-12MPa, holding pressure time 25-35s, foaming ratio 9.5-11.5 times, to obtain the soft cushion semi-finished product; e. Post-curing treatment: Cur the semi-finished soft pad at 65-75℃ for 1.5-2.5h, cool it to 25-30℃, and then cut it to obtain the composite soft pad.

[0020] Using the above technical solutions, raw material pretreatment can remove moisture and impurities from each component, ensuring the stability of subsequent process steps; premixing and dispersion can uniformly mix castor oil-based polyurethane prepolymer, polyolefin elastomer, multidimensional inorganic reinforcing filler, silane coupling agent, composite additive, chain extender catalyst, phase change composite filler, and phosphorus-nitrogen dynamic crosslinking long-lasting antistatic agent, reducing component agglomeration; melt blending can form a uniform melt system in the mixed slurry, and by controlling the temperature gradient and screw speed of each section of the extruder, the components can be fully integrated, and after pelleting... A uniform foaming masterbatch is obtained; foaming molding can be achieved by controlling the injection temperature, mold temperature, injection pressure, and holding time, so that the foaming masterbatch, composite foaming agent, and pore-filling regulator can form a soft pad semi-finished product with a specific cell structure; curing post-treatment can improve the structural stability of the soft pad semi-finished product, and after cutting, a composite soft pad with regular dimensions and stable performance is obtained; the synergistic effect of each step can make the prepared composite soft pad have good mechanical properties, cushioning properties, flame retardant properties, and antistatic properties, meeting the usage requirements of corner protection in glass packaging.

[0021] Preferably, in step e, the density of the finished composite cushion is 95-120 kg / m³. 3 .

[0022] Using the above technical solution, the density is 95-120 kg / m³. 3 The composite soft pad can form a soft structure that meets the needs of glass protection, and has both suitable flexibility and structural stability. The density range is matched with the fine closed-cell structure formed by the composite foaming agent, which can provide an effective energy absorption space for the impact during glass transportation and reduce the risk of glass breakage when it is impacted.

[0023] This invention also discloses a packaging method for a glass shatterproof packaging structure, comprising the following steps: S1. Initial protection of glass: Put a polyethylene antistatic plastic bag over the outside of the glass product, and then wrap it with a layer of expandable polyethylene pearl cotton. S2, Pad Installation: Attach the prepared composite pad to the four inner corners of the packaging box, and place the glass product packaged in step S1 inside. The side of the foam board away from the inner wall of the packaging box and the side of the composite pad away from the inner wall of the packaging box should be tightly attached to the outer packaging of the glass product. S3. Reinforcement: An inner wooden frame is installed on both sides of the outer packaging of the glass product. The outer side of the inner wooden frame is attached to the side of the foam board away from the inner wall of the packaging box and the side of the composite soft pad away from the inner wall of the packaging box. A rigid foam board is installed between the two long sides of the wooden frame. The two sides of the rigid foam board abut against the outer packaging of the glass product and the inner side of the packaging box, respectively. S4. Packaging and securing: Wrap anti-static tape around the outside of the packaging box and use strapping to double-pack it in a "cross" and "grid" pattern, with the strapping tension controlled at 60-80N.

[0024] Using the above technical solutions, the polyethylene antistatic plastic bag and expandable polyethylene pearl cotton can provide initial protection for the surface of glass products, reducing scratches and static electricity adsorption on the glass surface; the composite soft pad and foam board can provide cushioning protection for glass products and disperse the impact stress on the glass; the inner wooden frame can provide rigid support for glass products, and the rigid foam board can further fill the gaps and disperse stress, improving the overall stability of the packaging structure; the packing straps use a double packing method of "cross" and "grid" and control specific tension to ensure that the packaging structure fits tightly and is firmly fixed, reducing the shaking of glass products during transportation. The synergistic effect of each step can improve the impact resistance of glass products during transportation and reduce the probability of glass breakage.

[0025] The beneficial effects of this invention are as follows: Castor oil-based polyurethane prepolymer, used as the matrix of the composite cushion, provides basic flexibility, resilience, and moldability; polyolefin elastomers improve the toughness and elasticity of the composite cushion, increasing its elongation at break and impact strength; phase change composite fillers efficiently dissipate impact energy, enhancing cushioning and energy absorption; phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agents endow the composite cushion with both flame retardant and antistatic functions, while also improving material toughness; multidimensional inorganic reinforcing fillers improve the compressive strength of the composite cushion, disperse impact stress, and reduce material density; composite foaming agents enable the composite cushion to form a cell structure adapted to cushioning needs, providing space for energy absorption; silane coupling agents improve the interaction between inorganic fillers and... The interfacial bonding strength of the organic matrix reduces interfacial defects and improves the stability of mechanical properties; the composite additives can respectively inhibit thermo-oxidative aging, stabilize the cell structure, improve processing fluidity, inhibit mold growth, and improve the dispersibility of phase change components; the chain extender catalyst can accelerate the reaction between the matrix and the antistatic agent, and improve the mechanical strength and molding efficiency of the composite cushion; the pore filling regulator can fill the tiny pinholes generated during the foaming process, improve the cell density, and further optimize the cushioning performance; the above components work together to give the composite cushion good cushioning, flame retardancy, antistatic and mechanical properties. When combined with foam board and packaging box, it can provide effective protection for glass products. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the shatterproof glass packaging structure in this invention; In the diagram: 1. Packaging box; 2. Cushioning structure; 21. Foam board; 22. Composite cushioning; 23. Inner wooden frame; 24. Rigid foam board. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] The specific information on the raw materials used in the embodiments of the present invention is shown in Table 1.

[0029] Table 1

[0030]

[0031]

[0032] Example 1: like Figure 1As shown, this embodiment discloses a glass impact-resistant packaging structure, including a packaging box 1 and a cushioning structure 2 disposed within the packaging box 1. The cushioning structure 2 includes a foam board 21 and a composite soft pad 22, both of which are connected to the inner wall of the packaging box 1. By weight, the raw materials for preparing the composite soft pad 22 include: 45 parts castor oil-based polyurethane prepolymer, 8 parts polyolefin elastomer, 5 parts phase change composite filler, 6 parts phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, 4 parts multidimensional inorganic reinforcing filler, 6 parts composite foaming agent, 1 part silane coupling agent KH-550, 3.2 parts composite additives, 0.2 parts chain extender catalyst, and 0.2 parts polyethylene glycol PEG-600. The multidimensional inorganic reinforcing filler is composed of basalt whiskers and hollow glass microspheres compounded in a 1:1 mass ratio.

[0033] The composite foaming agent consists of 4 parts modified azodicarbonamide, 1 part talc, and 1 part sodium bicarbonate. The decomposition temperature of the modified azodicarbonamide is 150℃. The composite additive consists of 0.5 parts antioxidant 1010, 1 part polyether modified silicone oil, 0.3 parts zinc stearate, 0.2 parts 1,2-benzisothiazolin-3-one, and 1.2 parts ethylene-vinyl acetate copolymer. The chain extender catalyst is a compound of organic bismuth catalyst and dibutyltin dilaurate in a mass ratio of 1:1.

[0034] The phase change composite filler is halloysite / high-pressure resistant microcapsule paraffin phase change composite filler. By weight, its preparation raw materials include: 25 parts paraffin, 0.5 parts sodium dodecylbenzenesulfonate, 8 parts melamine, 20 parts formaldehyde solution with a mass fraction of 35%, 2 parts hexamethylenediamine, 0.5 parts triethanolamine, 0.5 parts nano silica, 8 parts halloysite nanotubes, 4 parts 3-aminopropyltriethoxysilane, 1.5 parts dopamine hydrochloride, 150 parts tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and 180 parts anhydrous toluene.

[0035] The preparation method of phase change composite filler includes the following steps: 1) Heat the paraffin to 55°C to melt it, add sodium dodecylbenzenesulfonate and three times the weight of the paraffin in deionized water, and stir at 1500 r / min for 30 min to form a uniform emulsion. 2) Melamine, formaldehyde solution, and hexamethylenediamine were mixed, nano-silica was added, and triethanolamine was added dropwise to adjust the pH of the system to 8.5. The mixture was stirred at 300 r / min for 1 h in a 70℃ water bath to obtain the prepolymer. 3) The prepolymer was added to the emulsion and stirred at 300 r / min at 80℃ for 3 h. After cooling to 25℃, it was centrifuged at 7000 r / min for 15 min. The precipitate was washed three times with anhydrous ethanol and then dried at 45℃ and vacuum degree -0.09 MPa for 7 h. After pulverizing, it was passed through a 200 mesh sieve to obtain nano-reinforced high pressure resistant microcapsules coated with paraffin. 4) Halloysite nanotubes were dried at 115℃ and vacuum degree -0.09MPa for 3h, cooled to 25℃ and added to anhydrous toluene. They were ultrasonically dispersed for 25min under ultrasonic power of 300W and frequency of 30kHz. 3-aminopropyltriethoxysilane was added, the temperature was raised to 80℃, and the reaction was refluxed for 6h under nitrogen protection and stirring at 300r / min. 5) After the reaction is complete, the reaction solution obtained in step 4) is centrifuged at 7000 r / min for 15 min. The precipitate is washed three times with anhydrous ethanol and then dried at 55℃ and vacuum degree -0.09MPa for 5 h to obtain aminated halloysite nanotubes. The aminated halloysite nanotubes are mixed with deionized water at a mass ratio of 1:10, dopamine hydrochloride is added, and the pH of the system is adjusted to 8.0 with tris(hydroxymethyl)aminomethane hydrochloride buffer. The reaction is stirred at 25℃ and 250 r / min for 10 h. 6) After the reaction is complete, the reaction solution obtained in step 5) is centrifuged at 7000 r / min for 15 min. The precipitate is washed three times with anhydrous ethanol and then dried at 55℃ and vacuum degree -0.09MPa for 7 h to obtain dopamine modified halloysite nanotubes. 7) Add the dopamine-modified halloysite nanotubes and the nano-reinforced high-pressure resistant microcapsules coated with paraffin obtained in step 3) to a high-speed mixer at a mass ratio of 1:1.2. Stir at 1200 r / min for 15 min at 55℃. After cooling to 25℃, grind and pass through a 200-mesh sieve to obtain the phase change composite filler.

[0036] The raw materials for preparing the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, by weight, include: 20 parts DOPO, 15 parts toluene diisocyanate, 0.2 parts dibutyltin dilaurate, 90 parts polyetheramine, and 0.4 parts polymethyl methacrylate microspheres.

[0037] The preparation method of phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent includes the following steps: (1) DOPO, toluene diisocyanate and dibutyltin dilaurate were added to the reactor, heated to 90°C, and stirred at 350 r / min for 3 h under nitrogen protection to obtain the intermediate; (2) Cool the intermediate to 55°C, add polyetheramine and polymethyl methacrylate microspheres, heat to 70°C, and stir at 250 r / min for 3 h to obtain a phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent.

[0038] The preparation method of the above-mentioned composite cushion includes the following steps: a. Raw material pretreatment: Castor oil-based polyurethane prepolymer and polyolefin elastomer were each dried at 75℃ and vacuum degree -0.09MPa for 3h; multidimensional inorganic reinforcing filler was dried at 105℃ for 1.5h; phase change composite filler was dried at 45℃ and vacuum degree -0.09MPa for 0.5h. b. Premixing and dispersing: The dried castor oil-based polyurethane prepolymer, the dried polyolefin elastomer, the dried multidimensional inorganic reinforcing filler, the silane coupling agent KH-550, the composite additives, and the chain extender catalyst are added to a high-speed mixer and stirred at 1300 r / min for 20 min at 25°C. Then, the dried phase change composite filler and the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent are added and stirred at 1600 r / min for 30 min at 40°C to obtain a mixed slurry. c. Melt blending: The mixture slurry is added to a twin-screw extruder. The temperature gradient of each section of the extruder is set as follows: Zone 1 140℃, Zone 2 150℃, Zone 3 160℃, and Die head 150℃. The screw speed is 250 r / min. After melt blending, the mixture is pelletized to obtain foamed masterbatch. d. Foaming molding: Mix the foaming masterbatch, composite foaming agent, and polyethylene glycol PEG-600 evenly, add it to the injection molding foaming machine, injection temperature 150℃, mold temperature 50℃, injection pressure 8MPa, holding time 25s, foaming ratio 9.5 times, to obtain the soft cushion semi-finished product. e. Post-curing treatment: Cur the semi-finished cushion at 65℃ for 1.5 hours, cool to 25℃, and then cut to obtain a density of 116 kg / m³. 3 Composite cushion.

[0039] This embodiment also discloses a packaging method for a glass shatterproof packaging structure, including the following steps: S1. Initial protection of glass: Put a polyethylene antistatic plastic bag over the outside of the glass product, and then wrap it with a layer of expandable polyethylene pearl cotton. S2, Pad Installation: Attach the prepared composite pad 22 to the four inner corners of the packaging box 1, and place the glass product packaged in step S1 inside. The side of the foam board 21 away from the inner wall of the packaging box 1 and the side of the composite pad 22 away from the inner wall of the packaging box 1 should be tightly attached to the outer packaging of the glass product. S3. Reinforcement: An inner wooden frame 23 is set on both sides of the outer packaging of the glass product. The outer side of the inner wooden frame 23 is attached to the side of the foam board 21 away from the inner wall of the packaging box 1 and the side of the composite soft pad 22 away from the inner wall of the packaging box 1. A rigid foam board 2421 is set between the two long sides of the wooden frame. The two sides of the rigid foam board 2421 abut against the outer packaging of the glass product and the inner side of the packaging box 1, respectively. S4. Packaging and securing: Wrap anti-static tape around the outside of the packaging box 1, and use packing straps for double packaging in a "cross" and "grid" pattern, with the tension of the packing straps controlled at 60N.

[0040] Example 2: This embodiment discloses a glass impact-resistant packaging structure, including a packaging box 1 and a cushioning structure 2 disposed within the packaging box 1. The cushioning structure 2 includes a foam board 21 and a composite cushion 22, both of which are connected to the inner wall of the packaging box 1. By weight, the composite cushion 22 is prepared from the following raw materials: 60 parts castor oil-based polyurethane prepolymer, 15 parts polyolefin elastomer, 12 parts phase change composite filler, 10 parts phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, 8 parts multidimensional inorganic reinforcing filler, 12 parts composite foaming agent, 3 parts silane coupling agent KH-560, 6.5 parts composite additives, 0.6 parts chain extender catalyst, and 0.5 parts polyethylene glycol PEG-600. The multidimensional inorganic reinforcing filler is composed of basalt whiskers and hollow glass microspheres in a mass ratio of 2:1.

[0041] The composite foaming agent consists of 8 parts modified azodicarbonamide, 2 parts talc, and 2 parts sodium bicarbonate. The decomposition temperature of the modified azodicarbonamide is 170℃. The composite additive consists of 1.5 parts antioxidant 1010, 2 parts polyether modified silicone oil, 0.8 parts zinc stearate, 0.6 parts 1,2-benzisothiazolin-3-one, and 1.6 parts ethylene-vinyl acetate copolymer. The chain extender catalyst is a compound of organic bismuth catalyst and dibutyltin dilaurate in a mass ratio of 2:1.

[0042] The phase change composite filler is halloysite / high-pressure resistant microcapsule paraffin phase change composite filler. By weight, its preparation raw materials include: 35 parts paraffin, 1.0 part sodium dodecylbenzenesulfonate, 12 parts melamine, 30 parts formaldehyde solution with a mass fraction of 37%, 4 parts hexamethylenediamine, 1.5 parts triethanolamine, 1.0 part nano silica, 12 parts halloysite nanotubes, 6 parts 3-aminopropyltriethoxysilane, 2.5 parts dopamine hydrochloride, 250 parts tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and 220 parts anhydrous toluene.

[0043] The preparation method of phase change composite filler includes the following steps: 1) Heat the paraffin to 65°C to melt it, add sodium dodecylbenzenesulfonate and 4 times the weight of deionized water, and stir at 2500 r / min for 50 min to form a uniform emulsion. 2) Melamine, formaldehyde solution, and hexamethylenediamine were mixed, nano-silica was added, and triethanolamine was added dropwise to adjust the pH of the system to 9.5. The mixture was stirred at 500 r / min for 2 h in an 80℃ water bath to obtain the prepolymer. 3) The prepolymer was added to the emulsion and stirred at 500 r / min for 5 h at 90 °C. After cooling to 30 °C, it was centrifuged at 9000 r / min for 25 min. The precipitate was washed 4 times with anhydrous ethanol and then dried at 50 °C and vacuum degree -0.095 MPa for 9 h. After pulverizing, it was passed through a 240 mesh sieve to obtain nano-reinforced high pressure resistant microcapsules coated with paraffin. 4) Halloysite nanotubes were dried at 125℃ and vacuum degree -0.095MPa for 5h, cooled to 30℃ and added to anhydrous toluene. They were ultrasonically dispersed for 35min under ultrasonic power of 400W and frequency of 40kHz. 3-aminopropyltriethoxysilane was added, the temperature was raised to 90℃, and the reaction was refluxed for 8h under nitrogen protection and stirring at 500r / min. 5) After the reaction is complete, the reaction solution obtained in step 4) is centrifuged at 9000 r / min for 25 min. The precipitate is washed 4 times with anhydrous ethanol and then dried at 65℃ and vacuum degree -0.095MPa for 7 h to obtain aminated halloysite nanotubes. The aminated halloysite nanotubes are mixed with deionized water at a mass ratio of 1:15, dopamine hydrochloride is added, and the pH of the system is adjusted to 8.5 with tris(hydroxymethyl)aminomethane hydrochloride buffer. The reaction is stirred at 350 r / min at 30℃ for 14 h. 6) After the reaction is complete, the reaction solution obtained in step 5) is centrifuged at 9000 r / min for 25 min. The precipitate is washed 4 times with anhydrous ethanol and then dried at 65℃ and vacuum degree -0.095MPa for 9 h to obtain dopamine modified halloysite nanotubes. 7) Add dopamine-modified halloysite nanotubes and paraffin-coated nano-reinforced high-pressure microcapsules obtained in step 3) to a high-speed mixer at a mass ratio of 1:1.8. Stir at 1800 r / min for 25 min at 65℃. After cooling to 30℃, grind and pass through a 240-mesh sieve to obtain phase change composite filler.

[0044] The raw materials for preparing the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, by weight, include: 25 parts DOPO, 20 parts toluene diisocyanate, 0.4 parts dibutyltin dilaurate, 110 parts polyetheramine, and 0.6 parts polymethyl methacrylate microspheres.

[0045] The preparation method of phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent includes the following steps: (1) DOPO, toluene diisocyanate and dibutyltin dilaurate were added to the reaction vessel, heated to 100°C, and stirred at 450 r / min for 5 h under nitrogen protection to obtain the intermediate; (2) Cool the intermediate to 65°C, add polyetheramine and polymethyl methacrylate microspheres, heat to 80°C, and stir at 350 r / min for 4 h to obtain a phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent.

[0046] The preparation method of the above-mentioned composite cushion includes the following steps: a. Raw material pretreatment: Castor oil-based polyurethane prepolymer and polyolefin elastomer were each dried at 85℃ and vacuum degree -0.095MPa for 5h; multidimensional inorganic reinforcing filler was dried at 115℃ for 2.5h; phase change composite filler was dried at 50℃ and vacuum degree -0.095MPa for 1.5h. b. Premixing and dispersing: The dried castor oil-based polyurethane prepolymer, the dried polyolefin elastomer, the dried multidimensional inorganic reinforcing filler, the silane coupling agent KH-560, the composite additives, and the chain extender catalyst are added to a high-speed mixer and stirred at 1500 r / min for 25 min at 30°C. Then, the dried phase change composite filler and the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent are added and stirred at 2000 r / min for 40 min at 50°C to obtain a mixed slurry. c. Melt blending: The mixture slurry is added to a twin-screw extruder. The temperature gradient of each section of the extruder is set as follows: Zone 1 150℃, Zone 2 160℃, Zone 3 170℃, and Die head 160℃. The screw speed is 350 r / min. After melt blending, the mixture is pelletized to obtain foamed masterbatch. d. Foaming molding: Mix the foaming masterbatch, composite foaming agent and polyethylene glycol PEG-600 evenly, add it to the injection molding foaming machine, injection temperature 160℃, mold temperature 60℃, injection pressure 12MPa, holding time 35s, foaming ratio 10.5 times, to obtain the soft cushion semi-finished product. e. Post-curing treatment: Cur the semi-finished cushion at 75℃ for 2.5 hours, cool to 30℃, and then cut to obtain a density of 105 kg / m³. 3 Composite cushion.

[0047] This embodiment also discloses a packaging method for a glass shatterproof packaging structure, including the following steps: S1. Initial protection of glass: Put a polyethylene antistatic plastic bag over the outside of the glass product, and then wrap it with a layer of expandable polyethylene pearl cotton. S2, Pad Installation: Attach the prepared composite pad 22 to the four inner corners of the packaging box 1, and place the glass product packaged in step S1 inside. The side of the foam board 21 away from the inner wall of the packaging box 1 and the side of the composite pad 22 away from the inner wall of the packaging box 1 should be tightly attached to the outer packaging of the glass product. S3. Reinforcement: An inner wooden frame 23 is set on both sides of the outer packaging of the glass product. The outer side of the inner wooden frame 23 is attached to the side of the foam board 21 away from the inner wall of the packaging box 1 and the side of the composite soft pad 22 away from the inner wall of the packaging box 1. A rigid foam board 2421 is set between the two long sides of the wooden frame. The two sides of the rigid foam board 2421 abut against the outer packaging of the glass product and the inner side of the packaging box 1, respectively. S4. Packaging and securing: Wrap anti-static tape around the outside of the packaging box 1, and use packing straps for double packaging in a "cross" and "grid" pattern, with the tension of the packing straps controlled at 80N.

[0048] Example 3: This embodiment discloses a glass impact-resistant packaging structure, including a packaging box 1 and a cushioning structure 2 disposed within the packaging box 1. The cushioning structure 2 includes a foam board 21 and a composite cushion 22, both of which are connected to the inner wall of the packaging box 1. By weight, the raw materials for preparing the composite cushion 22 include: 52 parts castor oil-based polyurethane prepolymer, 11 parts polyolefin elastomer, 8 parts phase change composite filler, 8 parts phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, 6 parts multidimensional inorganic reinforcing filler, 9 parts composite foaming agent, 2 parts silane coupling agent KH-570, 5 parts composite additives, 0.4 parts chain extender catalyst, and 0.3 parts polyethylene glycol PEG-600. The multidimensional inorganic reinforcing filler is composed of basalt whiskers and hollow glass microspheres compounded at a mass ratio of 1.5:1.

[0049] The composite foaming agent consists of 6 parts modified azodicarbonamide, 1.5 parts talc, and 1.5 parts sodium bicarbonate. The decomposition temperature of the modified azodicarbonamide is 160℃. The composite additive consists of 1 part antioxidant 1010, 1.5 parts polyether modified silicone oil, 0.5 parts zinc stearate, 0.4 parts 1,2-benzisothiazolin-3-one, and 1.4 parts ethylene-vinyl acetate copolymer. The chain extender catalyst is a compound of organic bismuth catalyst and dibutyltin dilaurate in a mass ratio of 1.5:1.

[0050] The phase change composite filler is halloysite / high-pressure resistant microcapsule paraffin phase change composite filler. By weight, its preparation raw materials include: 30 parts paraffin, 0.7 parts sodium dodecylbenzenesulfonate, 10 parts melamine, 25 parts formaldehyde solution with a mass fraction of 36%, 3 parts hexamethylenediamine, 1 part triethanolamine, 0.7 parts nano silica, 10 parts halloysite nanotubes, 5 parts 3-aminopropyltriethoxysilane, 2 parts dopamine hydrochloride, 200 parts tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and 200 parts anhydrous toluene.

[0051] The preparation method of phase change composite filler includes the following steps: 1) Heat the paraffin to 60°C to melt it, add sodium dodecylbenzenesulfonate and 4 times the weight of deionized water, and stir at 2000 r / min for 40 min to form a uniform emulsion. 2) Melamine, formaldehyde solution, and hexamethylenediamine were mixed, nano-silica was added, and triethanolamine was added dropwise to adjust the pH of the system to 9.0. The mixture was stirred at 400 r / min for 1.5 h in a 75°C water bath to obtain the prepolymer. 3) The prepolymer was added to the emulsion and stirred at 400 r / min at 85℃ for 4 h. After cooling to 28℃, it was centrifuged at 8000 r / min for 20 min. The precipitate was washed 4 times with anhydrous ethanol and then dried at 48℃ and vacuum degree -0.092 MPa for 8 h. After pulverizing, it was passed through a 220 mesh sieve to obtain nano-reinforced high pressure resistant microcapsules coated with paraffin. 4) Halloysite nanotubes were dried at 120℃ and vacuum degree -0.092MPa for 4h, cooled to 28℃ and added to anhydrous toluene. They were ultrasonically dispersed for 30min under ultrasonic power of 350W and frequency of 35kHz. 3-aminopropyltriethoxysilane was added, the temperature was raised to 85℃, and the reaction was refluxed for 7h under nitrogen protection and stirring at 400r / min. 5) After the reaction is complete, the reaction solution obtained in step 4) is centrifuged at 8000 r / min for 20 min. The precipitate is washed 4 times with anhydrous ethanol and then dried at 60℃ and vacuum degree -0.092 MPa for 6 h to obtain aminated halloysite nanotubes. The aminated halloysite nanotubes are mixed with deionized water at a mass ratio of 1:12, dopamine hydrochloride is added, and the pH of the system is adjusted to 8.2 with tris(hydroxymethyl)aminomethane hydrochloride buffer. The reaction is stirred at 300 r / min at 28℃ for 12 h. 6) After the reaction is complete, the reaction solution obtained in step 5) is centrifuged at 8000 r / min for 20 min. The precipitate is washed 4 times with anhydrous ethanol and then dried at 60℃ and vacuum degree -0.092 MPa for 8 h to obtain dopamine modified halloysite nanotubes. 7) Add the dopamine-modified halloysite nanotubes and the nano-reinforced high-pressure resistant microcapsules coated with paraffin obtained in step 3) to a high-speed mixer at a mass ratio of 1:1.5. Stir at 1500 r / min for 20 min at 60℃. After cooling to 28℃, grind and pass through a 220-mesh sieve to obtain the phase change composite filler.

[0052] The raw materials for preparing the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, by weight, include: 22 parts DOPO, 18 parts toluene diisocyanate, 0.3 parts dibutyltin dilaurate, 100 parts polyetheramine, and 0.5 parts polymethyl methacrylate microspheres.

[0053] The preparation method of phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent includes the following steps: (1) DOPO, toluene diisocyanate and dibutyltin dilaurate were added to the reactor, heated to 95°C, and stirred at 400 r / min for 4 h under nitrogen protection to obtain the intermediate; (2) Cool the intermediate to 60°C, add polyetheramine and polymethyl methacrylate microspheres, heat to 75°C, and stir at 300 r / min for 3.5 h to obtain a phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent.

[0054] The preparation method of the above-mentioned composite cushion includes the following steps: a. Raw material pretreatment: Castor oil-based polyurethane prepolymer and polyolefin elastomer were each dried at 80℃ and vacuum degree -0.092MPa for 4 hours; multidimensional inorganic reinforcing filler was dried at 110℃ for 2 hours; phase change composite filler was dried at 48℃ and vacuum degree -0.092MPa for 1 hour; b. Premixing and dispersing: The dried castor oil-based polyurethane prepolymer, the dried polyolefin elastomer, the dried multidimensional inorganic reinforcing filler, the silane coupling agent KH-570, the composite additives, and the chain extender catalyst are added to a high-speed mixer and stirred at 1400 r / min for 22 min at 28°C. Then, the dried phase change composite filler and the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent are added and stirred at 1800 r / min for 35 min at 45°C to obtain a mixed slurry. c. Melt blending: The mixture slurry is added to a twin-screw extruder. The temperature gradient of each section of the extruder is set as follows: Zone 1 145℃, Zone 2 155℃, Zone 3 165℃, and Die head 155℃. The screw speed is 300 r / min. After melt blending, the mixture is pelletized to obtain foamed masterbatch. d. Foaming molding: Mix the foaming masterbatch, composite foaming agent and polyethylene glycol PEG-600 evenly, add to the injection molding foaming machine, injection temperature 155℃, mold temperature 55℃, injection pressure 10MPa, holding time 30s, foaming ratio 11.5 times, to obtain the soft cushion semi-finished product. e. Post-curing treatment: Cur the semi-finished cushion at 70℃ for 2 hours, cool to 28℃, and then cut to obtain a density of 96kg / m³. 3 Composite cushion.

[0055] This embodiment also discloses a packaging method for a glass shatterproof packaging structure, including the following steps: S1. Initial protection of glass: Put a polyethylene antistatic plastic bag over the outside of the glass product, and then wrap it with a layer of expandable polyethylene pearl cotton. S2, Pad Installation: Attach the prepared composite pad 22 to the four inner corners of the packaging box 1, and place the glass product packaged in step S1 inside. The side of the foam board 21 away from the inner wall of the packaging box 1 and the side of the composite pad 22 away from the inner wall of the packaging box 1 should be tightly attached to the outer packaging of the glass product. S3. Reinforcement: An inner wooden frame 23 is set on both sides of the outer packaging of the glass product. The outer side of the inner wooden frame 23 is attached to the side of the foam board 21 away from the inner wall of the packaging box 1 and the side of the composite soft pad 22 away from the inner wall of the packaging box 1. A rigid foam board 2421 is set between the two long sides of the wooden frame. The two sides of the rigid foam board 2421 abut against the outer packaging of the glass product and the inner side of the packaging box 1, respectively. S4. Packaging and securing: Wrap anti-static tape around the outside of the packaging box 1, and use packing straps for double packaging in a "cross" and "grid" pattern, with the tension of the packing straps controlled at 70N.

[0056] Comparative Example 1: A glass impact-resistant packaging structure and its packaging method are disclosed, which differ from Example 3 only in that: no phase change composite filler is added, and a blend of dopamine-modified halloysite nanotubes (prepared using the same method as in Example 3) and paraffin is used instead, wherein the mass ratio of dopamine-modified halloysite nanotubes to paraffin is 1:1.5, and the mass of the blend is equal to the mass of the phase change composite filler in Example 3.

[0057] Comparative Example 2: A glass drop-resistant packaging structure and its packaging method differ from Example 3 only in that: no phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent is added; instead, a physical blend of triphenyl phosphate, polyetheramine D-2000, and 1,4-butanediol is used, with a weight ratio of 1:1:0.2, and the total weight of the physical blend is equal to the weight of the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent in Example 3.

[0058] Comparative Example 3: A glass shatterproof packaging structure and its packaging method are disclosed, which differ from Example 3 only in that no polyolefin elastomer is added.

[0059] Comparative Example 4: A glass shatterproof packaging structure and its packaging method are disclosed, which differ from Example 3 only in that the composite foaming agent does not contain nucleating agent talc, but only uses modified azodicarbonamide and sodium bicarbonate.

[0060] Comparative Example 5: A glass drop-resistant packaging structure and its packaging method are disclosed, which differ from Example 3 only in that no silane coupling agent (KH-570) is added.

[0061] Comparative Example 6: A glass drop-resistant packaging structure and its packaging method are disclosed, which differ from Example 3 only in that the multidimensional inorganic reinforcing filler uses only basalt whiskers and does not add hollow glass microspheres.

[0062] Comparative Example 7: A glass shatterproof packaging structure and its packaging method are disclosed, which differ from Example 3 only in that the injection pressure is reduced to 5 MPa in the foaming molding step.

[0063] Comparative Example 8: A glass shatterproof packaging structure and its packaging method are disclosed, which differ from Example 3 only in that the temperature of the three zones of the extruder is increased to 185°C in the melt blending step.

[0064] The material properties and overall packaging structure protective performance of the composite cushions obtained in Examples 1-3 and Comparative Examples 1-8 were tested. The testing methods and standards for each performance are as follows: (a) Performance testing of composite cushion materials 1. Mechanical properties Tensile strength / elongation at break: Tested according to "Determination of tensile properties of plastics - Part 1: General" (GB / T 1040.1-2018), Type I specimen, tensile rate 50 mm / min; Notched impact strength: Tested according to "Determination of impact strength of plastic cantilever beam" (GB / T 1843-2008), type A notch, notch depth 2mm; Compression rebound rate: Tested according to "Determination of compression properties of rigid foamed plastics" (GB / T 8813-2022), with a compression of 25%, held for 30 seconds, and a recovery of 30 seconds; Compression set: Tested according to "Determination of Compression Set of Flexible Foamed Plastics" (GB / T 6669-2008), 50% compression, 70℃, 22h; Cell structure characterization: Cell morphology was observed using scanning electron microscopy. Apparent density was determined according to "Determination of Apparent Density of Foamed Plastics and Rubber" (GB / T 6343-2009). Closed cell ratio was tested according to "Determination of Open and Closed Cell Ratio of Plastic Foamed Plastics" (GB / T12004.2-2009). Cell diameter was determined using image analysis.

[0065] 2. Functional Performance Flame retardant performance: The UL-94 vertical flammability rating was tested according to "Determination of flammability of plastics by horizontal and vertical methods" (GB / T 2408-2021), and the oxygen index was tested according to "Determination of flammability of plastics by oxygen index method - Part 2: Test at room temperature" (GB / T2406.2-2009). Long-lasting antistatic performance: The surface resistivity was tested according to the "Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials" (GB / T1410-2006). The test voltage was 500V, and the test conditions were 23℃ and humidity of 30%, 40%, 60% and 90%. The resistivity changes under different humidity conditions were recorded to verify the ion conduction mechanism. Moist heat aging resistance: Tested according to "Determination of Moist Heat Aging Resistance of Thermoplastic Plastics" (GB / T 1035-2008), 60℃, 90% humidity, 30 days, the tensile strength retention rate after aging was tested, and the tensile strength retention rate was calculated as (tensile strength after aging / original tensile strength) × 100%. Phase change energy absorption performance: Differential scanning calorimetry was used to test the phase change latent heat and the phase change latent heat retention rate after 10 thermal cycles. The phase change latent heat retention rate was calculated as (phase change latent heat after 10 thermal cycles / original phase change latent heat) × 100%. Thermal stability: The thermogravimetric analysis was performed according to the standard GB / T 19466.3-2004, "Determination of mass loss and decomposition temperature of plastic samples by thermogravimetric analysis (TGA)", with a heating rate of 10℃ / min, and the mass loss rate was tested at 170℃ for 30 min.

[0066] (II) Testing of the overall packaging structure's protective performance Using 5mm thick tempered glass (300mm×300mm) as the test sample, and with the complete packaging structure, all tests were performed in parallel for 5 times, and the average value was taken. Drop test: According to the "Basic Tests for Packaging and Transport Packages - Part 1: Impact Test Method" (GB / T4857.1-2005) and ISTA 1A standard, the glass was dropped freely from a height of 1m, 1.5m, and 2m respectively. The drop posture included flat surface, long side, short side, and corner. The glass breakage rate was recorded. The breakage rate was calculated as (number of broken samples / total number of samples) × 100%, avoiding absolute statements. Impact absorption energy: Tested according to the "Dynamic Compression Test Method for Packaging Cushioning Materials" (GB / T 18301-2001), a 5kg hammer impacts the soft padding part of the glass corner from a height of 1m, and the impact absorption energy is recorded. Reusability: The packaging structure was subjected to 10 drops from a height of 1.5m at a corner. The glass breakage rate and the amount of soft padding deformation were tested after the 10th drop. The amount of deformation was calculated as (thickness after deformation - original thickness) / original thickness × 100%. Long-lasting antistatic environmental adaptability: The surface resistivity of the packaging structure was tested according to GB / T 1410-2006 under humidity conditions of 30%, 40%, 60%, and 90% to verify the humidity dependence.

[0067] The results are shown in Tables 2, 3 and 4.

[0068] Table 2. Test results of mechanical properties of composite cushion materials

[0069] Table 3. Test results of functional performance of composite cushion materials

[0070] Table 4. Test results of the overall packaging structure's protective performance

[0071] Using Example 3 as the control group, the performance differences and causes of Comparative Examples 1-8 are analyzed as follows: Comparative Example 1: No phase change composite filler was added; instead, an equal weight mixture of dopamine-modified halloysite nanotubes and paraffin was used. Compared to Example 3, the tensile strength decreased from 1.05 MPa to 0.60 MPa (a decrease of 42.9%), the elongation at break decreased from 395% to 255% (a decrease of 35.4%), and the notched impact strength decreased from 21.0 kJ / m. 2 Reduced to 12.8 kJ / m 2 (A decrease of 39.0%), compression rebound rate decreased from 94.5% to 84.2% (a decrease of 10.9%), compression set increased from 3.9% to 8.9% (an increase of 128.2%), and finished product density increased from 96 kg / m³. 3 Increased to 117kg / m 3 (Increase of 21.9%), pore diameter increased from 50-60μm to 80-90μm, closed-cell rate decreased from 75% to 63% (decrease of 16.0%), oxygen index decreased from 32.5% to 23.8% (decrease of 26.8%), and surface resistivity (40%-90% RH) increased from 1.8×10⁻⁶. 9 Ω increased to 5.9×10 11The tensile strength retention rate after 30 days of damp heat aging decreased from 98.2% to 87.8% (a decrease of 10.6%), the glass breakage rate after a 2m drop reached 60%, the deformation of the soft pad after 1.5m × 10 drops increased from 3.5% to 13.2% (an increase of 277.1%), the impact absorption energy decreased from 59.2J to 35.8J (a decrease of 39.5%), and the glass breakage rate after the 10th 1.5m drop reached 40%. The reasons for the aforementioned performance degradation are as follows: unencapsulated paraffin is prone to melting and leakage at injection molding foaming temperatures of 150-160℃, making it difficult to form a stable phase change energy absorption system, resulting in cell structure collapse (increased density, coarsened cells, and decreased closed-cell rate); in addition, the compatibility between inorganic fillers and the matrix interface decreases, the risk of inorganic filler agglomeration increases, and interface defects increase, leading to a comprehensive decline in the material's mechanical properties and durability; furthermore, with the absence of phase change composite fillers, the nano-SiO2 in the microcapsule wall material cannot be uniformly dispersed through the microcapsule wall material, failing to exert the interface reinforcement and flame retardant synergistic effect, while the melting and leakage of paraffin damages the cell structure, resulting in uneven dispersion of flame retardant components, ultimately causing a significant decrease in the oxygen index and a drop in the flame retardant rating from V-0 to V-2.

[0072] Comparative Example 2: No phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent was added; instead, an equal weight mixture of triphenyl phosphate, polyetheramine D-2000, and 1,4-butanediol was used. Compared to Example 3, the glass breakage rate after a 2m drop reached 25%, the deformation of the cushion after 1.5m × 10 drops increased from 3.5% to 8.5% (an increase of 142.9%), the impact absorption energy decreased from 59.2J to 40.5J (a decrease of 31.6%), the glass breakage rate after the 10th 1.5m drop reached 20%, and the surface resistivity (40%-90% RH) increased from 1.8 × 10⁻⁶. 9 Ω increased to 8.9×10 10 Ω, surface resistivity (30% RH) from 1.6 × 10 11 Ω increased to 8.5×10 12 The reason is that triphenyl phosphate and polyetheramine D-2000 are only physically blended, lacking the phosphorus-nitrogen synergistic flame retardant system and hydrogen bond dynamic crosslinking network constructed by the chemical grafting of DOPO-toluene diisocyanate and polyetheramine in phosphorus-nitrogen dynamic crosslinking long-lasting antistatic agents; 1,4-butanediol only acts as a small molecule chain extender and cannot form a chemical grafting reaction with DOPO and polyetheramine, cannot construct a hydrogen bond dynamic crosslinking network, and cannot achieve reversible dissipation of impact energy, resulting in a significant decrease in the material's impact energy dissipation capacity; at the same time, the ungrafted polyetheramine D-2000 has too strong migration and is easily washed away by water or lost by friction, and cannot form a stable surface conductive layer, causing the antistatic performance to fail and the surface resistivity to increase by one order of magnitude.

[0073] Comparative Example 3: No polyolefin elastomer added. Compared with Example 3, tensile strength decreased from 1.05 MPa to 0.55 MPa (a decrease of 47.6%), elongation at break decreased from 395% to 195% (a decrease of 50.6%), and notched impact strength decreased from 21.0 kJ / m. 2 Reduced to 10.5 kJ / m 2 (A decrease of 50.0%), compression rebound rate decreased from 94.5% to 81.2% (a decrease of 14.1%), compression set increased from 3.9% to 9.6% (an increase of 146.2%), the breakage rate of glass dropped from a height of 2m reached 80%, the impact absorption energy decreased from 59.2J to 30.8J (a decrease of 48.0%), the breakage rate of glass dropped from 1.5m for the 10th time reached 60%, and the deformation of the soft pad after 1.5m × 10 drops increased from 3.5% to 15.8% (an increase of 351.4%). The reason is that the polyolefin elastomer and the bio-based polyurethane matrix form an interpenetrating elastic network, which endows the material with high elongation at break and compression rebound properties; without this component, the soft foam system lacks the toughening and supporting effect of the elastomer phase, and the overall mechanical properties and cushioning support performance are significantly reduced. Under impact load, it is prone to brittle fracture and irreversible plastic deformation, resulting in a sharp deterioration in cushioning performance and reusability.

[0074] Comparative Example 4: Composite foaming agent without nucleating agent talc. Compared with Example 3, the cell diameter increased from 50-60 μm to 90-100 μm, the closed-cell rate decreased from 75% to 55% (a decrease of 26.7%), the compression rebound rate decreased from 94.5% to 87.5% (a decrease of 7.4%), the glass breakage rate after a 2m drop reached 15%, and the deformation of the cushion after 1.5m × 10 drops increased from 3.5% to 8.2% (an increase of 134.3%). The reason is that talc, as a nucleating agent, provides heterogeneous nucleation sites during the foaming process, inducing the formation of a fine and uniform closed-cell structure, while inhibiting cell merging. Without the nucleating agent, cell growth lacks effective control, resulting in cell coarsening and merging, a significant decrease in the closed-cell rate, and stress concentration and cell collapse under impact, leading to a significant reduction in buffering performance and structural stability.

[0075] Comparative Example 5: No silane coupling agent added. Compared with Example 3, the tensile strength decreased from 1.05 MPa to 0.70 MPa (a decrease of 33.3%), the elongation at break decreased from 395% to 275% (a decrease of 30.4%), and the notched impact strength decreased from 21.0 kJ / m. 2 Reduced to 14.5 kJ / m 2(A decrease of 31.0%), compression rebound rate decreased from 94.5% to 85.8% (a decrease of 9.2%), compression set increased from 3.9% to 8.1% (an increase of 107.7%), 30-day wet heat aging tensile strength retention rate decreased from 98.2% to 89.0% (a decrease of 9.4%), the breakage rate of glass dropped from a height of 2m reached 40%, the impact absorption energy decreased from 59.2J to 39.8J (a decrease of 32.8%), the breakage rate of glass dropped from 1.5m for the 10th time reached 30%, and the deformation of the soft pad after 1.5m × 10 drops increased from 3.5% to 11.2% (an increase of 220.0%). The reason is that silane coupling agents improve the interfacial compatibility between phase change composite fillers, multidimensional inorganic reinforced fillers and organic matrices through chemical bonding; without silane coupling agents, the interfacial bonding force between inorganic fillers and matrices is weak, forming a large number of interfacial defects and stress concentration points, which leads to accelerated decay of mechanical properties, especially intensified interfacial debonding under humid and hot environments, resulting in a significant decrease in aging resistance and long-term buffering performance.

[0076] Comparative Example 6: The multidimensional inorganic reinforcing filler used only basalt whiskers, without the addition of hollow glass microspheres. Compared with Example 3, the compression set increased from 3.9% to 4.5% (an increase of 15.4%), while the changes in other mechanical and functional properties were relatively small (<15%). The density of the finished product increased slightly to 98 kg / m³. 3 The reason is that the absence of hollow glass microspheres leads to a decrease in stress dispersion ability and an increase in residual strain after repeated compression; however, basalt whiskers, as the main reinforcing phase, can still provide effective mechanical support, so apart from permanent compression deformation, other properties are not significantly degraded.

[0077] Comparative Example 7: The injection pressure in the foaming molding step was reduced to 5 MPa. Compared with Example 3, the tensile strength decreased from 1.05 MPa to 0.75 MPa (a decrease of 28.6%), the elongation at break decreased from 395% to 305% (a decrease of 22.8%), and the notched impact strength decreased from 21.0 kJ / m. 2 Reduced to 15.8 kJ / m 2 (A decrease of 24.8%), compression rebound rate decreased from 94.5% to 86.5% (a decrease of 8.5%), compression set increased from 3.9% to 7.6% (an increase of 94.9%), and finished product density increased from 96 kg / m³. 3 Increased to 115kg / m 3(Increase of 19.8%), cell diameter increased from 50-60μm to 85-95μm, closed-cell rate decreased from 75% to 60% (decrease of 20.0%), glass breakage rate after a 2m drop reached 30%, impact absorption energy decreased from 59.2J to 42.8J (decrease of 27.7%), glass breakage rate after the 10th 1.5m drop reached 20%, and deformation of the cushioning material after 1.5m × 10 drops increased from 3.5% to 9.6% (increase of 174.3%). The reason is that the injection pressure of 8-12MPa is matched with the pressure resistance of the microcapsules and the foaming system, ensuring complete melt filling and a fine cell structure; when the pressure is reduced to 5MPa, the melt filling is insufficient and gas expansion is uncontrolled, leading to coarsening of the cells, a decrease in closed-cell rate, and an increase in density, resulting in a comprehensive deterioration of the material's cushioning performance and mechanical properties.

[0078] Comparative Example 8: The temperature in the three zones of the extruder during the melt blending step was increased to 185°C. Compared to Example 3, the tensile strength decreased from 1.05 MPa to 0.60 MPa (a decrease of 42.9%), the elongation at break decreased from 395% to 225% (a decrease of 43.0%), and the notched impact strength decreased from 21.0 kJ / m². 2 Reduced to 11.2 kJ / m 2 (A decrease of 46.7%), compression rebound rate decreased from 94.5% to 82.3% (a decrease of 12.9%), compression set increased from 3.9% to 9.1% (an increase of 133.3%), UL-94 rating decreased from V-0 to V-1, oxygen index decreased from 32.5% to 27.8% (a decrease of 14.5%), 30-day wet heat aging tensile strength retention decreased from 98.2% to 84.8% (a decrease of 13.6%), and the latent heat retention rate after 10 thermal cycles decreased from... The breakage rate decreased from 95.1% to 68.5% (a decrease of 28.0%), the mass loss rate at 180℃ / 10MPa increased from 2.5% to 15.6% (an increase of 524.0%), the breakage rate of glass dropped from a height of 2m reached 50%, the impact absorption energy decreased from 59.2J to 33.8J (a decrease of 42.9%), the breakage rate of glass dropped from 1.5m for the 10th time reached 35%, and the deformation of the soft pad after 1.5m×10 drops increased from 3.5% to 12.2% (an increase of 248.6%). The reasons are as follows: 185℃ exceeds the processing temperature of the polyurethane matrix, causing thermal degradation of the matrix molecular chains and a significant decrease in melt strength. At the same time, the paraffin in the phase change composite filler melts and seeps out prematurely at high temperatures, resulting in the loss of phase change material (a surge in mass loss rate and a sharp drop in the latent heat retention rate of phase change). In addition, high temperature causes the cell structure to become uncontrolled, further aggravating the deterioration of mechanical properties and flame retardant properties. Furthermore, the castor oil-based polyurethane matrix undergoes thermal degradation at high temperatures, and the molecular chains break, causing a complete collapse in mechanical properties and durability.

[0079] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A glass impact-resistant packaging structure, characterized in that, It includes a packaging box (1) and a buffer structure (2) disposed inside the packaging box (1). The buffer structure (2) includes a foam board (21) and a composite soft pad (22). Both the foam board (21) and the composite soft pad (22) are connected to the inner wall of the packaging box (1). The raw materials for preparing the composite cushion (22) by weight include: 45-60 parts of castor oil-based polyurethane prepolymer, 8-15 parts of polyolefin elastomer, 5-12 parts of phase change composite filler, 6-10 parts of phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, 4-8 parts of multidimensional inorganic reinforcing filler, 6-12 parts of composite foaming agent, 1-3 parts of silane coupling agent, 3.2-6.5 parts of composite additives, 0.2-0.6 parts of chain extender catalyst, and 0.2-0.5 parts of pore filling regulator.

2. The glass impact-resistant packaging structure according to claim 1, characterized in that, The multidimensional inorganic reinforcing filler is composed of basalt whiskers and hollow glass microspheres in a mass ratio of 1-2:

1. The silane coupling agent is one of KH-550, KH-560 or KH-570. The pore filling regulator is polyethylene glycol PEG-600.

3. The glass impact-resistant packaging structure according to claim 1, characterized in that, The composite foaming agent is composed of 4-8 parts of modified azodicarbonamide, 1-2 parts of talc, and 1-2 parts of sodium bicarbonate, wherein the modified azodicarbonamide has a decomposition temperature of 150-170℃; the composite additive is composed of 0.5-1.5 parts of antioxidant 1010, 1-2 parts of polyether modified silicone oil, 0.3-0.8 parts of zinc stearate, 0.2-0.6 parts of 1,2-benzisothiazolin-3-one, and 1.2-1.6 parts of ethylene-vinyl acetate copolymer; the chain extender catalyst is composed of an organic bismuth catalyst and dibutyltin dilaurate in a mass ratio of 1-2:

1.

4. The glass impact-resistant packaging structure according to claim 1, characterized in that, The phase change composite filler is halloysite / high-pressure resistant microcapsule paraffin phase change composite filler. By weight, its preparation raw materials include: 25-35 parts paraffin, 0.5-1.0 parts sodium dodecylbenzenesulfonate, 8-12 parts melamine, 20-30 parts formaldehyde solution with a mass fraction of 35-37%, 2-4 parts hexamethylenediamine, 0.5-1.5 parts triethanolamine, 0.5-1.0 parts nano silica, 8-12 parts halloysite nanotubes, 4-6 parts 3-aminopropyltriethoxysilane, 1.5-2.5 parts dopamine hydrochloride, 150-250 parts tris(hydroxymethyl)aminomethane hydrochloride buffer solution, and 180-220 parts anhydrous toluene.

5. The glass impact-resistant packaging structure according to claim 4, characterized in that, The preparation method of the phase change composite filler includes the following steps: 1) Heat the paraffin to 55-65℃ to melt it, add sodium dodecylbenzenesulfonate and 3-4 times the weight of deionized water, and stir at 1500-2500 r / min for 30-50 min to form a uniform emulsion. 2) Mix melamine, formaldehyde solution, and hexamethylenediamine, add nano-silica, and add triethanolamine dropwise to adjust the pH of the system to 8.5-9.

5. Stir the mixture in a water bath at 70-80℃ at a speed of 300-500r / min for 1-2 hours to obtain the prepolymer. 3) Add the prepolymer to the emulsion and stir at 300-500 r / min at 80-90℃ for 3-5 h. After cooling to 25-30℃, centrifuge at 7000-9000 r / min for 15-25 min. Wash the precipitate with anhydrous ethanol 3-4 times, and then dry it at 45-50℃ and vacuum degree -0.09~-0.095 MPa for 7-9 h. After pulverizing, pass it through a 200-240 mesh sieve to obtain nano-reinforced high pressure resistant microcapsule-coated paraffin. 4) Dry halloysite nanotubes at 115-125℃ and vacuum degree -0.09~-0.095MPa for 3-5h, cool to 25-30℃ and add to anhydrous toluene. Sonicate disperse for 25-35min under ultrasonic power of 300-400W and frequency of 30-40kHz. Add 3-aminopropyltriethoxysilane, heat to 80-90℃ and reflux for 6-8h under nitrogen protection and stirring at 300-500r / min. 5) After the reaction is complete, the reaction solution obtained in step 4) is centrifuged at 7000-9000 r / min for 15-25 min. The precipitate is washed 3-4 times with anhydrous ethanol and then dried at 55-65℃ and vacuum degree -0.09~-0.095MPa for 5-7 h to obtain aminated halloysite nanotubes. The aminated halloysite nanotubes are mixed with deionized water at a mass ratio of 1:10-15, dopamine hydrochloride is added, and the pH of the system is adjusted to 8.0-8.5 with tris(hydroxymethyl)aminomethane hydrochloride buffer. The mixture is stirred at 250-350 r / min at 25-30℃ for 10-14 h. 6) After the reaction is complete, the reaction solution obtained in step 5) is centrifuged at 7000-9000 r / min for 15-25 min. The precipitate is washed with anhydrous ethanol 3-4 times, and then dried at 55-65℃ and vacuum degree -0.09~-0.095MPa for 7-9 h to obtain dopamine modified halloysite nanotubes. 7) Add dopamine-modified halloysite nanotubes and paraffin-coated nano-reinforced high-pressure microcapsules obtained in step 3) to a high-speed mixer at a mass ratio of 1:1.2-1.

8. Stir at 1200-1800 r / min for 15-25 min at 55-65℃. After cooling to 25-30℃, grind and pass through a 200-240 mesh sieve to obtain phase change composite filler.

6. The glass impact-resistant packaging structure according to claim 1, characterized in that, The raw materials for preparing the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent, by weight, include: 20-25 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 15-20 parts of toluene diisocyanate, 0.2-0.4 parts of dibutyltin dilaurate, 90-110 parts of polyetheramine, and 0.4-0.6 parts of polymethyl methacrylate microspheres.

7. The glass shatterproof packaging structure according to claim 6, characterized in that, The preparation method of the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent includes the following steps: (1) 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, toluene diisocyanate and dibutyltin dilaurate were added to a reaction vessel, heated to 90-100℃, and stirred at 350-450r / min for 3-5h under nitrogen protection to obtain an intermediate; (2) Cool the intermediate to 55-65℃, add polyetheramine and polymethyl methacrylate microspheres, heat to 70-80℃, stir at 250-350r / min for 3-4h to obtain phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent.

8. The glass impact-resistant packaging structure according to any one of claims 1-7, characterized in that, The preparation method of the composite cushion (22) includes the following steps: a. Raw material pretreatment: The castor oil-based polyurethane prepolymer and polyolefin elastomer are dried at 75-85℃ and a vacuum of -0.09 to -0.095 MPa for 3-5 hours; the multidimensional inorganic reinforcing filler is dried at 105-115℃ for 1.5-2.5 hours; and the phase change composite filler is dried at 45-50℃ and a vacuum of -0.09 to -0.095 MPa for 0.5-1.5 hours. b. Premixing and dispersing: The dried castor oil-based polyurethane prepolymer, the dried polyolefin elastomer, the dried multidimensional inorganic reinforcing filler, the silane coupling agent, the composite additive, and the chain extender catalyst are added to a high-speed mixer and stirred at 1300-1500 r / min at 25-30℃ for 20-25 min. Then, the dried phase change composite filler and the phosphorus-nitrogen type dynamic crosslinking long-lasting antistatic agent are added and stirred at 1600-2000 r / min at 40-50℃ for 30-40 min to obtain a mixed slurry. c. Melt blending: The mixture slurry is added to a twin-screw extruder. The temperature gradient of each section of the extruder is set as follows: Zone 1 140-150℃, Zone 2 150-160℃, Zone 3 160-170℃, and the die head 150-160℃. The screw speed is 250-350 r / min. After melt blending, the mixture is pelletized to obtain foamed masterbatch. d. Foaming molding: Mix the foaming masterbatch, composite foaming agent, and pore filling regulator evenly, add it to the injection molding foaming machine, injection temperature 150-160℃, mold temperature 50-60℃, injection pressure 8-12MPa, holding pressure time 25-35s, foaming ratio 9.5-11.5 times, to obtain the soft cushion semi-finished product; e. Post-curing treatment: Curing the semi-finished soft pad at 65-75℃ for 1.5-2.5h, cooling to 25-30℃, and then cutting to obtain the composite soft pad (22).

9. The glass impact-resistant packaging structure according to claim 8, characterized in that, In step e, the density of the finished composite cushion (22) is 95-120 kg / m³. 3 .

10. A packaging method for a glass shatterproof packaging structure according to claim 8, characterized in that, Includes the following steps: S1. Initial protection of glass: Put a polyethylene antistatic plastic bag over the outside of the glass product, and then wrap it with a layer of expandable polyethylene pearl cotton. S2, Pad Installation: The prepared composite pad (22) is pasted on the four inner corners of the packaging box (1), and the glass product packaged in step S1 is placed in it. The side of the foam board (21) away from the inner wall of the packaging box (1) and the side of the composite pad (22) away from the inner wall of the packaging box (1) are tightly attached to the outer packaging of the glass product. S3, reinforcement: Inner wooden frames (23) are set on both sides of the outer packaging of the glass product. The outer side of the inner wooden frame (23) is attached to the side of the foam board (21) away from the inner wall of the packaging box (1) and the side of the composite soft pad (22) away from the inner wall of the packaging box (1). A rigid foam board (24) is set between the two long sides of the wooden frame. The two sides of the rigid foam board (24) are respectively attached to the outer packaging of the glass product and the inner side of the packaging box (1). S4. Packaging and securing: Wrap antistatic tape around the outside of the packaging box (1) and use packing straps for double packaging in a "cross" and "grid" pattern. The tension of the packing straps should be controlled at 60-80N.